(untitled) (Medico Legal Update, 2021)
Objective: evaluate the serum level of Glycodeline-A, sFlt-1, PlGF combined with ?hCGas predictor markers of first trimester pregnancy loss in Iraqi women . Method: A case-contol study, carried out from April 2019 to March 2020 and included 85 women, 40 of them as patients which have abortion at the first trimester and 45 of them as healthy control which haven, t any complication at the same time of gestation, investigations included serum measurements of ?hCG, Glycodeline-A, sFlt-1, PlGF By Method ELISA. Results: Serum Niveaus?hCG, sFlt-1 Was major higher in healthy controls than in patients, while serum level of Glycodeline-A, PlGF was significantly lower in healthy control than in patients, and there is no significant correlation among each of age with other parameters, and there is no significant correlation among each of gest.age with Glycodeline-A and sFlt-1, while there is significant correlation among each of ges.age with ?hCG and PlGF P<0.05. Conclusion: The present study suggested the significant role of Glycodeline-A, sFlt-1, PlGF in pathogenesis of first trimester pregnancy loss and some of them was related to ?hCGin this period and the age of patients wasn, t effect on all of these parameters.